First ever case report of co-occurrence of hobnail variant of papillary thyroid carcinoma and intrathyroid parathyroid adenoma in the same thyroid lobe. (2020) - Al-Yahri, Omer; Abdelaal, Abdelrahman; El Ansari, Walid; Farghaly, Hanan; Murshed, Khaled; Zirie, Mahmoud A.; Al Hassan, Mohamed S.
Highlights: First reported case of hobnail variant of papillary thyroid cancer and Intrathyroid parathyroid adenoma occurring within same thyroid lobe. Next-generation sequencing of the mutation spectrum of hobnail variant of papillary thyroid cancer showed BRAFV600E mutation. Studies that define other molecular abnormalities may be useful as therapeutic targets. Abstract: Introduction: The hobnail variant of papillary thyroid cancer (PTC) is rare. Intrathyroid parathyroid adenoma (ITPA) is also rare. Co-ocurrence of PTC and ITPA in the same thyroid lobe is extremely rare. Likewise, primary hyperparathyroidism with such non-medullary thyroid carcinoma is rare. The specific molecular profile of hobnail PTC (HPTC) is different from the classic, poorly differentiated and anaplastic variants and may contribute to its aggressive behavior. HPTC's genetic profile remains unclear. Presentation of case: A 61-year-old woman presented to our endocrine clinic with generalized aches, bone pain, polyuria, and right neck swelling of a few months' duration. Laboratory findings revealed hypercalcemia and hyperparathyroidism. Ultrasound of the neck showed 4.6 cm complex nodule within the right thyroid lobe. Sestamibi scan suggested parathyroid adenoma in the right thyroid lobe. Fine-needle aspiration (FNA) revealed atypical follicular lesion of undetermined significance. She underwent right lobectomy, which normalized the intraoperative intact parathyroid hormone levels. Final pathology with immunohistochemical stains demonstrated HPTC and IPTA (2 cm each). Next-generation sequencing investigated the mutation spectrum of HPTC and detected BRAFV600E mutation. Conclusions: A parathyroid adenoma should not exclude the diagnosis of thyroid carcinoma. Thyroid evaluation is needed for patients with primary hyperparathyroidism to prevent missing concurrent thyroid cancers. Cytomorphologic features to distinguish thyroid from parathyroid cells on FNA cytology must be considered. Immunohistochemical stains are important. BRAFV600E is the most common mutation in HPTC. This is possibly the first reported case of HPTC and ITPA co-occurring within the same thyroid lobe. Studies that define other molecular abnormalities may be useful as therapeutic targets.